2019
DOI: 10.1002/mrm.27670
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of microvascular cerebral blood volume changes over the cardiac cycle with ferumoxytol‐enhanced T2* MRI

Abstract: Purpose This feasibility study investigates the non‐invasive measurement of microvascular cerebral blood volume (BV) changes over the cardiac cycle using cardiac‐gated, ferumoxytol‐enhanced T2∗ MRI. Methods Institutional review board approval was obtained and all subjects provided written informed consent. Cardiac gated MR scans were prospectively acquired on a 3.0T scanner in 22 healthy subjects using T2∗‐weighted sequences with 2D‐EPI and 3D spiral trajectories. Images were collected before and after the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 48 publications
0
7
1
Order By: Relevance
“…The observed systolic cardiac-induced tissue expansion is induced by the blood volume pulsations of the microvascular bed embedded in the tissue. Rivera et al reported average relative volume pulsations of 0.3•10 -3 for gray matter and 0.1•10 -3 for white matter, respectively [129]. These values are somewhat lower than our measurements, which is probably related to differences in methodology.…”
Section: Discussioncontrasting
confidence: 80%
“…The observed systolic cardiac-induced tissue expansion is induced by the blood volume pulsations of the microvascular bed embedded in the tissue. Rivera et al reported average relative volume pulsations of 0.3•10 -3 for gray matter and 0.1•10 -3 for white matter, respectively [129]. These values are somewhat lower than our measurements, which is probably related to differences in methodology.…”
Section: Discussioncontrasting
confidence: 80%
“…Other novel and potentially relevant alternatives to well-established techniques are MRI sequences relying on the T2* signal to quantify microvascular blood volume change over the cardiac cycle. 26,27 A challenge in such approaches are low signal-to-noise levels, something that may be resolved using a contrast injection. 27 Although time-resolved MRI generally put constraints on the signal-to-noise levels (because of subdividing available data into individual time frames), our proposed 4D flow MRI approach was able to obtain waveforms that appeared to be based on enough samples to produce a virtually noise-free representation of the distal cerebral arterial waveform (Suppl.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 In addition, the T2* signal has been used to characterize microvascular blood volume change over the cardiac cycle. 26,27 4D flow MRI makes it possible to measure time-resolved blood flow velocities with sub-millimeter resolution and whole-brain coverage. 2830 In previous studies, 4D flow MRI has been used to quantify pulsatility in large cerebral arteries by measuring blood flow at specific cross sections of interest.…”
Section: Introductionmentioning
confidence: 99%
“…Realizing the opportunities, challenges and caveats of assessing renal haemodynamics and tissue oxygenation in vivo and non‐invasively, probing renal BVf is highly relevant if not essential for the pursuit of renal MR oximetry . Intravenously applied superparamagnetic iron oxide nanoparticle (USPIO) preparations can be used as MRI visible blood pool markers for probing alterations in BVf, in particular ferumoxytol, which is increasingly used off‐label as an intravascular MRI contrast agent . To promote these advancements at the interface between physics, physiology and patient care, this review discusses the opportunities of ferumoxytol‐enhanced assessment of renal BVf.…”
Section: Introductionmentioning
confidence: 99%
“…42 Intravenously applied superparamagnetic iron oxide nanoparticle (USPIO) preparations can be used as MRI visible blood pool markers for probing alterations in BVf, in particular ferumoxytol, which is increasingly used off-label as an intravascular MRI contrast agent. [42][43][44][45][46][47] To promote these advancements at the interface between physics, physiology and patient care, this review discusses the opportunities of ferumoxytol-enhanced assessment of renal BVf. For this purpose, the specifics of renal oxygenation and perfusion are outlined first.…”
mentioning
confidence: 99%